"My Crying Is Not a Cry by Itself": Building Sustainable Social Ties through a Poor People's Organization. (May 2020) - Mazelis, Joan Maya
Research has highlighted that social ties help poor people to survive, but has also shown that nonkin ties often only last a short time. In this article, I argue that organizations that serve the needs of poor people can help to create more sustainable supportive ties among them. Drawing on participant observation and ethnographic interviews with twenty-five members of the Kensington Welfare Rights Union (KWRU) in Philadelphia—an organization of, by, and for poor people—I found that supportive ties among members of KWRU can last years or even decades. I show how this organization enabled poor people to create and maintain supportive ties. KWRU provided people living in desperate poverty space for frequent interaction, connection, and cooperation. The organization supported a sense of kinship among members, and group leaders often helped to mend rifts between members. While KWRU is distinctive, other organizations that serve the needs of poor people could use this model to be more responsive to the needs of those in poverty.